2016
DOI: 10.1073/pnas.1522639113
|View full text |Cite
|
Sign up to set email alerts
|

Identification of three LRR-RKs involved in perception of root meristem growth factor in Arabidopsis

Abstract: A peptide hormone, root meristem growth factor (RGF), regulates root meristem development through the PLETHORA (PLT) stem cell transcription factor pathway, but it remains to be uncovered how extracellular RGF signals are transduced to the nucleus. Here we identified, using a combination of a custom-made receptor kinase (RK) expression library and exhaustive photoaffinity labeling, three leucine-rich repeat RKs (LRR-RKs) that directly interact with RGF peptides in Arabidopsis. These three LRR-RKs, which we nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
128
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 27 publications
(33 reference statements)
8
128
0
2
Order By: Relevance
“…Therefore, we believe that RGIs, at least RGI1, qualify as the receptors of RGF1. This conclusion is consistent with recent independent studies from two other research groups [55,56]. Matsubayashi's group used a photoaffinity approach and identified three RGF1 receptors in Arabidopsis [55], which are identical to our RGI1 to RGI3.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, we believe that RGIs, at least RGI1, qualify as the receptors of RGF1. This conclusion is consistent with recent independent studies from two other research groups [55,56]. Matsubayashi's group used a photoaffinity approach and identified three RGF1 receptors in Arabidopsis [55], which are identical to our RGI1 to RGI3.…”
Section: Discussionsupporting
confidence: 91%
“…This conclusion is consistent with recent independent studies from two other research groups [55,56]. Matsubayashi's group used a photoaffinity approach and identified three RGF1 receptors in Arabidopsis [55], which are identical to our RGI1 to RGI3. On the other hand, Chai's group identified the same 5 RGF1 receptors as we show here based on the presence of conserved RXR and RXGG signature motifs in the extracellular domains of these receptors [56].…”
Section: Discussionsupporting
confidence: 91%
“…During the preparation of the manuscript, three LRRRLKs, corresponding to RGFRs 1, 3 and 4 identified in the current study, were reported to be involved in RGF perception [30]. In addition, an accompanying study [31] identified the same five LRR-RLKs as receptors for RGFs by using a completely different approach from ours, further supporting the validity of our biochemical assay for matching of receptors and their ligands.…”
Section: Identification Of Receptors For Rgfssupporting
confidence: 75%
“…For coexpression, resuspended bacteria containing different constructs were mixed with equal OD 600 of 0.4. After 46 h, 10 nM RGF1 or 1 µM PSK [30] was infiltrated into tobacco leaves, while double-distilled water was infiltrated as mock. All leaves were harvested after 2 h of infiltration.…”
Section: Transient Expression In Nicotiana Benthamianamentioning
confidence: 99%
“…Just before the pair of papers were published in Cell Research, another group [12], using RLK expression library and photoaffinity-labeled RGF1, identified three RLKs of the same family to function as RGF receptors. Following the identification of the RGF peptides [4], Matsubayashi group began to explore the possibility of RLK family members as RGF receptors.…”
mentioning
confidence: 99%